Metabolic assessment of perfused livers using magnetic resonance imaging and spectroscopy - Young, LAJ (2021)
Liver transplantation is the only definitive treatment for end-stage liver disease. However, a shortage of suitable donor organs means that currently up to 30% of patients become too ill or die before ever receiving a transplant. Normothermic machine perfusion (NMP) offers a potential solution by reducing preservation injury which might enable the safe transplantation of higher-risk livers, thereby expanding the donor pool and reducing waiting list mortality. To achieve the full potential of machine perfusion in transplantation, a set of sensitive and specific biomarkers are needed to enable accurate prediction of a donated livers ability to survive the transplantation process and function in the recipient. Unfortunately, such a set of biomarkers is not yet established.